RESPON MASYARAKAT TERHADAP PENGELOLAAN HUTAN RAKYAT DI DESA MANTIKOLE - Dina Anggraini; Adam Malik; herman harijanto (Jurnal Warta Rimba, 2019)
Community forest is one of the initiatives of the government in order to overcome the fulfillment of the community's needs for timber forest products, adding to the number of forest areas that have been reduced due to natural forests which have suffered a lot of degradation and de-concentration. The benefits that can be obtained from community forest management include fulfillment of timber needs, increased community income and increased productivity of community land. The purpose of this study was to determine the understanding and response of the community towards community forest management carried out by the community of farmer groups in Mantikole Village, West Dolo District, Sigi Regency. This research was conducted for three months from December to February 2019 in Mantikole Village, West Dolo District, Sigi Regency. The number of samples in this study were 30 respondents who were obtained using a random method, the respondents consisted of village officials, community leaders, traditional leaders, youth leaders, community forest farmer groups, and farmers not community forests. The data analysis method used in this study is descriptive analysis. The results of the study show that most of the people (respondents) agree to rakayat forest management. The understanding of the people of Mantikole Village is classified as low in rakayat forest management, but the response of the community is high in rakayat forest management and the community hopes that they can increase economic income through rakayat forest management.